Network selection and resource allocation for multicast in HetNets - Ma, Maode (2014)
In a heterogeneous wireless system, the member stations of a multicast stream may be distributed in many networks within the system. Meanwhile, each member station may have multiple network interfaces available simultaneously. Therefore, the selection of networks for serving the stream and the allocation of radio resources in the selected networks play significant roles in improving the utilization of system resource, especially for the stream with a large group size. In this paper, a novel joint network selection and resource allocation scheme is proposed aiming to minimize the overall resources consumed by the multicast stream in the heterogeneous wireless system. The fundamental idea is to gather the member stations located at the same network region and to transmit the stream with possibly high modulation and coding rates. We first formulate the scheme as a binary integer programming problem, and then derive a computationally efficient Lagrangian-based heuristic algorithm to solve the problem, where the architecture of interworking system is taken into account. Simulation results show that the proposed scheme will cost the minimum system bandwidth compared to other reference schemes.